(untitled) (Bangladesh Journal of Zoology, 2021)
For the removal of undesired fish species from aquaculture ponds, an alternative to synthetic toxins is the use of botanical toxicants which are biodegradable and environmentally safer. Toxicological effects of distilled water, 50% ethyl alcohol, methanol and acetone extracts of three indigenous plant seeds, Jatropha carcus (Linn.), Hydnocarpus wightianus (Blume) and Aleurites moluccana (Linn. Willd) were studied on the predatory fish, Heteropneustes fossilis (Bloch) under normal laboratory conditions. Depending upon the type of plants, extracts and concentrations, percentage mortality varied. Behavioral activities increased with increasing concentrations. During exposure, fish exhibited discolouration, gulping for air, erratic swimming, loss of reflex, slow movement and ultimately became motionless before death . The extent of toxicity of extracts for J. carcus, H. wightianus and A. moluccana on H. fossilis could be ranked in the order: Acetone > methanol > 50% ethyl alcohol > distilled water. On the basis of LC50 values the most toxic was acetone extract of J. carcus seeds and least toxic was distilled water extract of A. moluccana seeds. It is suggested that these plant seed extracts would be helpful in aquaculture to remove unwanted fish species from culture ponds. Bangladesh J. Zool. 48(2): 379-391, 2020